Response of oligotrophic coastal microbial populations in the SE Mediterranean Sea to crude oil pollution; lessons from mesocosm studies. (5th February 2021) - Shai, Yael; Rubin-Blum, Maxim; Angel, Dror L.; Sisma-Ventura, Guy; Zurel, Dror; Astrahan, Peleg; Rahav, Eyal
Abstract: Anthropogenically-induced oil spills release large amounts of organic pollutants into the marine environment. To date, little is known about the response of microbial populations (biomass, activity and diversity) to crude oil pollution in Low Nutrients Low Chlorophyll and warm systems. Here, we investigated the daily dynamics of phytoplankton and heterotrophic bacteria in response to an oil spill (500 μm thick layer) in the coastal waters of the SE Mediterranean Sea (SEMS), using mesocosms during winter and summer. Crude oil addition caused a marked decrease in phytoplankton biomass (40–76%) and production rates (22–96%), whereas heterotrophic bacterial abundance and production increased (4–68% and 17–165%, respectively). Concurrently, amplicon sequencing of the 16S rRNA gene revealed that oil-degrading bacteria became abundant 48–96 h post-oil addition, while the cosmopolitan Synechococcus and SAR11 lineages were significantly reduced (by 78–98% and 59–98%, respectively). Fertilization with inorganic nutrients (NO3 and PO4 ) reduced the deleterious effects of the oil, resulting in a less distinct reduction in phytoplankton biomass/abundance. Our results highlight the potential of intrinsic microbial communities to degrade oil-derived pollutants in oligotrophic coastal waters. Graphical abstract: Image 1 Highlights: Ramifications of oil spills were studied in the SE Mediterranean Sea coastal water. Crude-oil addition resulted in decreased abundances of Synechococcus and SAR11. Hydrocarbon degraders became abundant following crude oil amendment. N+P addition reduced the inhibitory effects of oil pollution to phytoplankton.